2019
DOI: 10.3390/ma12071039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Aging on Asphalt Modified Using Microwave Activation Crumb Rubber

Abstract: Effective approaches are required to be developed to solve the poor compatibility and thermal stability problems of crumb rubber-modified asphalt (CRMA). This study focuses on a method called microwave activation. However, seldom researches pay attention to the properties of MACRMA after aging. The objective of this study was to prepare microwave-activated CRMA (MACRMA) and investigate the performance of asphalt after aging. The samples were subjected to thin-film oven test (TFOT) at different times and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…The rubberized bitumen contained CR with 40-mesh size had a smaller ∆ T 1 compared with the rubberized bitumen contained CR activated by microwave. During the STA at 163 °C, the swelling reaction and degradation of CR will gradually advance [ 36 , 44 ]. Therefore, the main reactions happening in STA can be divided into the aging of bitumen and the swelling and degradation of CR.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The rubberized bitumen contained CR with 40-mesh size had a smaller ∆ T 1 compared with the rubberized bitumen contained CR activated by microwave. During the STA at 163 °C, the swelling reaction and degradation of CR will gradually advance [ 36 , 44 ]. Therefore, the main reactions happening in STA can be divided into the aging of bitumen and the swelling and degradation of CR.…”
Section: Results and Analysismentioning
confidence: 99%
“…Xiaolong Yang [ 20 ] determined that CR modified by microwave activation had a more efficient swelling reaction than CR. The recoverability of microwave-activated rubberized bitumen was improved after aging [ 36 ]. However, the desulfurization and degradation give rise to the attenuation of CR’s elastic property, which decreased the resistance to fatigue cracking for rubberized bitumen after aging.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have been carried out on asphalt rubber for use as a road material [ 3 , 4 , 5 ]. Multistress creep recovery and frequency sweep tests were used to determine the rheological properties, i.e., the high-temperature and fatigue properties, of asphalt rubber mixed with a warm agent and a liquid antistripping agent, as well as of SBS (styrene-butadiene-styrene) biorubber asphalt [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xu introduced that an activated crumb rubber method using an ultrasonic focusing apparatus could more significantly improve the compatibility between the activated crumb rubber and neat asphalt binder [19]. Recently, microwave irradiation has been used for CRM pre-treatment before blending with an asphalt binder to improve the properties of rubber-asphalt blends in China [20,21]. Many studies have confirmed that higher surface activity and improved compatibility with asphalt due to microwave radiation treatment cleft the surface vulcanization network of the CRM [22].…”
Section: Introductionmentioning
confidence: 99%